Pengaruh Gaya Kepemimpinan, Kompensasi Dan Motivasi Terhadap Kepuasan Kerja Karyawan Pada PT Kerry Nex Express - Cecep Haryoto; Brenda Dinda Salsabila; Agus Suradika (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This study aims to test and analyze the influence of leadership style, compensation and motivation on employee job satisfaction at PT. Kerry Nex Express. The independent variables used are leadership style, compensation and motivation, while the dependent variable is job satisfaction. The method of collecting data is carried out by distributing questionnaires to 60 employees of PT. Kerry Nex Express. The use of quantitative methods which are associations as research methods that use primary data. The results showed that the t-count value was -1.431 <2.00 and the significance was 0.158> 0.05 so the leadership style did not affect employee job satisfaction, the t-count value was 1.768> 2.00 and the significance was 0.000 <0.05 so compensation affect employee job satisfaction, from the calculated t value of 5.329 > 2.00 and a significance of 0.000 <0.05 so motivation affects employee job satisfaction. While simultaneously leadership style, compensation and motivation affect employee job satisfaction as seen from the calculated F value of 44.218 > 2.76 and a significant value of 0.000 <0.05.